The use of active methodologies in the prevention of enterobiasis in the elderly: Experience report - Modesto, Maria Fernanda Nascimento; Assis, Natália Reis de; Pimentel, Daniela França; Pontes, Ana Rosa Botelho; Bitar, Maria Amélia Fadul; Lopes, Márcia Maria Bragança; Pimenta, Bruna Marques; Gomes, Franciane do Socorro Rodrigues (Seven Editora, 2024)
Introduction: Enterobius Vermiculares is the parasite that causes enterobiasis, a very prevalent disease in Brazil, with many signs and/or symptoms that impair the quality of life of the population, especially the elderly who, due to issues related to natural aging, decreased self-care, and living conditions, demonstrate the need for greater attention and care by health professionals. Education and health, combined with active methodologies, educational technologies, and social participation, can act in the prevention of this disease. Objective: To report the experience of nursing students regarding the use of active methodologies in the prevention of enterobiasis in the elderly. Methodology: This is an experience report with a qualitative approach regarding the health action carried out by nursing students participating in the extension project "Promotion of knowledge about intestinal parasitosis with elderly people in situations of socioeconomic vulnerability", in November 2023, in the waiting room of the Hiperdia Program (Hypertension and Diabetes Program) of a basic health unit in Belém do Pará. The use of active methodologies such as styrofoam prototypes, illustrative posters and gamification were used in the educational action. Results and Discussions: The action demonstrated that most of the elderly had already contracted enterobiasis, popularly known by all as "tuxin", with anal pruritus being the sign and symptom most reported by the group. As for the preventive and control measures of this disease, the group demonstrated that the most feasible are hand washing and nail trimming, while the others that require costs and depend on basic sanitation infrastructure were considered more difficult to adopt. Health education identified that although enterobiasis is a recurrent and known disease, the vast majority did not understand the mechanisms of contamination and prevention. The educational materials designed and built specifically for the elderly were relevant instruments and facilitators of interaction, approach, participation and retention of knowledge about this disease. It was evidenced the need to invest in health actions, far beyond just exposing information, to plan teaching efficiently, to think about active methodologies that allow bonding with the elderly, with experiences and knowledge, which make them participative and, therefore, autonomous, critical and capable of making decisions about their own health, also based on the in scientific knowledge. Conclusion: In view of the results of the educational action, it was evidenced that the elderly are qualified to adopt preventive measures against enterobiasis and to share such knowledge with family members and the community, in order to improve quality of life and social well-being. DOI:https://doi.org/10.56238/sevened2024.001-015